CAD information handling for obtaining dependable manufacturing systems - Miron, E. (2016)
The design of mechatronic systems is a multidisciplinary task that involves skills from mechanic, electronic and informatics areas. Recently, the expertise from such different fields is able to communicate and exchange the necessary contribution to successful design solutions, through a myriad of internet tools available. The introduction of internet of services on the design of mechatronic systems, mainly when teams, with different skills, operate in different geographic places, has contributed to flawlessly integrate better and interoperable final solutions. The design of mechatronic systems without errors that operate without failures - is an important contribution to such goal. Safe behavior of mechatronic systems is crucial, mainly, in what concerns human safety. The correct behavior of those systems can be improved by the development of safe software for their controllers using some analysis techniques. Among them, Formal Verification (FV) is able to guarantee the best results. One of the main gaps using this technique is the difficulty of obtaining adequate plant models, in a systematic way, because this task is, usually, related with high level of expertise of designers and, in industry, this fact causes some difficulties for using those methods and tools. The work presented in this paper is a part of a larger project developed in the context of Software as a Service (SaaS) platform. It is intended to develop a systematized approach in order to obtain meaningful plant models out of existing CAD data, from Autodesk Inventor (or CATIA), and translate those models to formatted files according to input data of the UPPAAL model checker (because it allows dealing with time variable).The main idea is to obtain, systematically, plant models for Formal Verification purposes, considering that nowadays companies with different CAD systems are using increasingly often STEP-File format. A solution for this specific problem is explored and presented in this paper.